Ocular pulse amplitude in patients with open angle glaucoma, normal tension glaucoma, and ocular hypertension. Issue 9 (1st September 2002) - Schwenn, O; Troost, R; Vogel, A; Grus, F; Beck, S; Pfeiffer, N
Abstract : Background/aim: Intraocular pressure (IOP) is not a fixed constant value but rather has pulsatile components associated with cardiac action. The SmartLens dynamic observing tonometer (odc, Ophthalmic Development Company AG, Zurich, Switzerland) can measure and record simultaneously IOP and ocular pulse amplitude (OPA). It was the aim of this study to evaluate OPA in patients with primary open angle glaucoma (POAG) and high IOP, normal tension glaucoma (NTG), and ocular hypertension (OHT). Furthermore, the authors examined whether there were any correlations with blood pressure. Methods: 80 subjects were divided into four groups (n=20): 20 patients each with POAG, NTG, and OHT and 20 volunteers without any ocular pathology except for cataract served as a control group. Results: The OPA of the POAG group was not statistically significant different from the control group and from the OHT group. However, OPA was statistically significant lower (p<0.01) in the NTG group compared with all other groups. The OPA of the OHT group was slightly higher compared to the healthy volunteers (p=0.09) and to the POAG patients (p=0.09). No statistically significant correlations with blood pressure could be detected. A logistic regression model was established which identified OPA as an independent risk factor for NTG. Conclusions: The study demonstrated a decrease in OPA of patients suffering from NTG. Thus, measuring of OPA by the SmartLens dynamic observing tonometer could be helpful in the detection of NTG patients.